A Longitudinal Study Evaluating the Impact of 0.01% Atropine in High Myopic Children (RAMCOM-II Study) - Pradeep Agarwal; Veenu Maan; Ashi Khurana; Samir Sutar; Lokesh Chauhan (Journal of Current Ophthalmology, 2024)
Purpose: To assess the safety and efficacy of the 4-year administration of 0.01% atropine following a 1-year observation period in high myopic children. Methods: The RAMCOM-II study continues the RAMCOM study, designed as an interventional nonrandomized study. Participants were observed for 1 year without any intervention to establish a baseline. Subsequently, children were divided into two arms: participants in the intervention group received one drop of 0.01% atropine daily at bedtime from years 1 to 5, while the control arm received no treatment and was monitored with routine clinical examinations. Annual assessments captured myopia progression, visual acuity, adverse events, and compliance. Statistical analyses compared outcomes between the two groups, considering demographic factors. Results: At the 4-year follow-up, myopia progression from baseline in the intervention group (atropine-treated eyes) was significantly lower than in the control group (2.0 ± 2.0 diopter [D] vs. 3.2 ± 1.9 D, P = 0.01). Axial elongation also favored the intervention group. At the 5-year follow-up, similar trends persisted, underscoring the sustained efficacy of 0.01% atropine. Myopia progression remained significantly reduced in the intervention group compared to the control group (2.2 ± 2.0 D vs. 3.4 ± 1.9 D, P = 0.01). Although differences in axial elongation were less pronounced, these findings highlight the long-term benefits of 0.01% atropine in managing high myopia in children. Conclusion: The RAMCOM-II study supports the efficacy of 0.01% atropine in controlling myopia progression over 5 years, emphasizing its promising role in pediatric high myopia management.